PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VC SD NEGERI 136 PEKANBARU - Nur Afni; Lazim N Lazim N; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low learning at SD Negeri 136 Pekanbaru class VC. It can be seen from their final examination results with an average score of 57,5 when the success is 75. In order to solve this problem, the which starts with students’ involvement in thinking by themselves after reading the materials provided, followed by reading and developing ideas with their peers and then followed by writing conclusion and reports. This research is an action research which consits of two cycles. Cycle I consits of two meetings and one daily exam at the end of every cycle. The subject of this research isthe SD Negeri 136 Pekanbaru class of VC which contains of 40 students, consisting of 19 females and 21 males. Before the learning model cooperative script was applied, the teacher activity in cycle I improved from 66,67% which is categorized as well , to 79,17% which is categorized as good as well. Adn then it increased again in cycle II and became 87,5% which is categorized as very good, to 93,83% which is categorized as very good. Then student activity in cycle I improved from 62,5% which is categorized as well, to 70,83% which which is categorized as well. And then it increased again in cycle II and became 83,33% which is categorized as good as well, to 91,76% which is categorized as very good. The students’ learning outcomes increased from 57,5 to 69,63 in daily exam I and it improved again in daily exam II, becoming 78,13. With the implementation of learning model cooperative script,the students’ learning outcomes improve by 20,63. Therefore it can be conluded that the implementation of the learning model cooperative script can increased the learning outcomes of Social Subjects at the SD Negeri 136 Pekanbaru class of VC.Keywords: Learning Model Cooperative Script, Learning Result, Social Studies